Talleres de estilos de crianza para padres de familia del nivel inicial - Balarezo Velasco, Mauricio Miguel (2022)
The following proposal is based on “Workshops for Parents of the Initial Level” it is based on 15 workshops, its objective has as priority to strengthen family ties, creates an emotional family bond, taking into account that each and every member of the household transmits values, affections, attitudes and ways of being, which makes the child assimilate from birth. That is why family life is the first school of the infant, what it takes to spend time and effort, the proposal is aimed at motivating parents to raise awareness about the time they spend at home, how they handle their emotions with children, especially the importance of motivating infants to perform certain activities which are difficult for them to do. The validation of experts and user has been essential to carry out the aforementioned proposal, since their years of experience endorse them for the review of each and every one of the workshops, thus determining the effectiveness and importance of the Workshops for Parents of the Initial Level. For all the aforementioned, it has been concluded that the workshops for parents, since through participation they acquire tools to understand, understand and communicate more assertively with their children and thus support and encourage their learning, at the same time, concrete mechanisms are established to strengthen the responsibility of parents regarding the upbringing of their children while transmitting values, emotions, trust and the involvement of the integral development of the child.